PENGARUH EKSPOR DAN IMPOR TERHADAP CADANGAN DEVISA INDONESIA - Novita Fitriani, Yeny; Christian Sitohang, Arga; Rahmadiana, Sinta; Putra Oentoro, Yosse; Khotimah, Khosnol; Indriyanti, Eki; Feriadi, Feriadi; Syahrul Maulana, Muhammad (LP2M Universitas Bina Bangsa, 2025)
The growth of Indonesia's economy demonstrates the country's growing economic integration with the global economy. All of this is a result of globalization's open economic system, where everything is interdependent and interdependent on everything else. Every country's economy relies on international commerce to some extent. Countries are encouraged to participate in the arena of international commerce in this modern period. In international commerce, foreign currency reserves are a crucial instrument and source of funding. The net position of the foreign assets of the government and foreign exchange institutions is what is required to fund imports, and Bank Indonesia is in charge of managing these reserves. Due to their ever-changing value, a country's foreign currency reserves are subject to testing in order to determine how various variables, such as export and import volumes, affect their position